Reviving the Trinity: Making Mary of Guelders’ 15th Century built legacy relevant in 21st-century Scotland - Rachel Delman; Jill Harrison (Royal Studies Journal, 2025)
In 1460, Mary of Guelders embarked on an ambitious charitable foundation in Edinburgh, the magnificent Trinity collegiate chapel and hospital, intended to proclaim Scotland’s outward looking aspiration to figure on a European stage. In 1848 the buildings were demolished to make way for the expansion of Waverley Station. The stones were abandoned on Calton Hill, with the council promising to relocate and restore the building. After twenty years of ineffectual vacillation, the now much reduced heap of stones was used to construct Trinity Apse at the bottom of Chalmers Close, on the edge of Edinburgh’s Old Town. This article argues that today, this significant but little known and under-utilised heritage asset, one of the oldest buildings in the UNESCO World Heritage site of the city of Edinburgh, deserves full recognition for its historical significance and its considerable potential to meet multi-stakeholder needs in a complex twenty-first century urban environment. Building on research that demonstrates the power of authenticity, and historically informed storytelling in particular, for achieving affective and impactful heritage and tourism experiences, we argue that the royal origin story of Trinity Apse makes a compelling case for achieving visitor engagement steeped in authenticity and affect. Decisions made by the city council in the late nineteenth century are interrogated in order to demonstrate how the concerns and values of multiple stakeholders have been mapped onto the building historically, and how they might usefully inform decision-making regarding Mary of Guelders’ architectural treasure at another pivotal moment in the building’s future.